1999
DOI: 10.1073/pnas.96.22.12269
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-enhanced ortho-para conversion in solid hydrogen up to 58 GPa

Abstract: We measured the ortho-para conversion rate in solid hydrogen by using Raman scattering in a diamond-anvil cell, extending previous measurements by a factor of 60 in pressure. We confirm previous experiments that suggested a decrease in the conversion rate above about 0.5 GPa. We observe a distinct minimum at 3 GPa followed by a drastic increase in the conversion rate to our maximum pressure of 58 GPa. This pressure enhancement of conversion is not predicted by previous theoretical treatments and must be due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…No difference is observed, reflecting the fact that, in the corresponding density range, the anisotropic interaction is too weak to structure an orientational order of the liquid. The present data have been obtained on liquids with the normal concentration since below 5 GPa the conversion rate between J = 0 and J = 1 states should be very slow [29,30]. It has been shown that the anisotropic interaction is dominated by the electric quadrupole-quadrupole interaction up to at least 40 GPa and so it should change rapidly under compression, as 5/3 [31].…”
mentioning
confidence: 60%
“…No difference is observed, reflecting the fact that, in the corresponding density range, the anisotropic interaction is too weak to structure an orientational order of the liquid. The present data have been obtained on liquids with the normal concentration since below 5 GPa the conversion rate between J = 0 and J = 1 states should be very slow [29,30]. It has been shown that the anisotropic interaction is dominated by the electric quadrupole-quadrupole interaction up to at least 40 GPa and so it should change rapidly under compression, as 5/3 [31].…”
mentioning
confidence: 60%
“…This assumes equilibration of the ort ho/para concentrations, however, the nuclear spins equilibrate on the timescale of a typical experiment [22], and so ort ho-peaks are initially visible even at 10 K. We account for this by redefining the density matrix aŝ…”
Section: The Hindered-rotor Hamiltonian and Wave Functionmentioning
confidence: 99%
“…The quantum mechanical character of H 2 (D 2 ) assures that nuclear spins can be parallel or anti-parallel, resulting in two different species of H 2 (D 2 ), referred to as ortho and para states. 26 Both pressure and temperature have an important role in controlling the population of the different ortho/para species, 29,30 and thus controlling the intensity ratio between the ortho/para rotons. To avoid any influence on the proposed roton thermometry method, intensity ratios between ortho/ortho and para/para rotons were only considered.…”
Section: B H2(d2) Temperature Measurements Using Raman Spectroscopy:mentioning
confidence: 99%